Umifenovir and coronavirus infections: a review of research results and clinical practice - I. A. Leneva; N. Y. Pshenichnaya; V. A. Bulgakova (Терапевтический архив, 2020)
Coronaviruses are known to cause acute respiratory infections. Antiviral therapy, including for COVID-19, is based on clinical practice, experimental data and trial results. The purpose of this review is to: provide and systematize actual preclinical data, clinical trials results and clinical practice for antiviral agent umifenovir (Arbidol). Databases Scopus, Web of Science, RSCI and medRxiv were used for publication searching from 2004. A meta-analysis of clinical trials results was performed. Umifenovir is antiviral agent, it belongs to fusion inhibitors, interacts with SARS-CoV-2 spike protein. Umifenovir the impede the trimerization of spike glycoprotein and inhibit host cell adhesion, at the level of the coronaviruses S-protein of interaction with ACE2 receptor. Preclinical studies in vitro and on animals show umifenovir activity against a number of coronaviruses, including SARS-CoV, MERS-CoV, SARS-CoV-2, and others. Umifenovir, in combination with other antiviral drugs, symptomatic or traditional medicine, was used in China to treat patients with COVID-19, resulting in reduced mortality, virus elimination, the frequency of more severe course and complications in middle severity. However, antiviral therapy for the treatment of severe patients, with ARDS, did not lead to improved outcomes. In comparative clinical studies, umifenovir showed similar effectiveness with other antiviral drugs, and lower frequency of adverse reactions. Therapy with umifenovir, led to an increase percentage of patients with negative results of PCR tests on days 714 (I2=69.8%, RR 0.48, 95% CI 0.190.76; p=0.001). The efficacy and safety of antivirals against SARS-CoV-2 still requires clinical investigation. Moderate forms of COVID-19 could be effectively treated by antivirals, but severe forms of COVID-19, characterized by pulmonary immunopathology, require different approaches to treatment.